Threshold Behavior of hard X rays in Resonant Transition Radiation from Beryllium Foils preprint Hiroshima University HUPD-9412 - Andreyashkin M. Yu.; Kaplin V. V. Valeriy Viktorovich; Uglov S. R. Sergey Romanovich; Zabaev V. N. Viktor Nikolaevich; Endo I.; Kobayashi T. (Hiroshima, 1994)
В фонде НТБ ТПУ отсутствует